Detachment of droplets from cylinders in flow using an experimental analogue - Hotz, C.; Mead-Hunter, Ryan; Becker, Thomas; King, A.; Wurster, S.; Kasper, G.; Mullins, B. (Cambridge University Press, 2015)
This work experimentally examines the detachment of liquid droplets from both oleophilic and oleophobic fibres, using an atomic force microscope. The droplet detachment force was found to increase with increasing fibre diameter and forces were higher for philic fibres than phobic fibres. We also considered the detachment of droplets situated on the intersection of two fibres and arrays of fibres (such as found in fibrous mats or filters) and found that the required detachment forces were higher than for similarly sized droplets on a single fibre, though not as high as expected based on theory. A model was developed to predict the detachment force, from single fibres, which agreed well with experimental results. It was found that the entire dataset (single and multiple fibres) could be best described by power law relationships.